Multidisciplinary personalized approach in the management of vulvar cancer ‐ the Vul.Can Team experience. Issue 7 (July 2020) - Tagliaferri, Luca; Garganese, Giorgia; D'Aviero, Andrea; Lancellotta, Valentina; Fragomeni, Simona Maria; Fionda, Bruno; Casà, Calogero; Gui, Benedetta; Perotti, Germano; Gentileschi, Stefano; Inzani, Frediano; Corrado, Giacomo; et al.
ABSTRACT : Introduction : Multidisciplinary treatment strategy involving adjuvant radiotherapy for advanced vulvar cancer could be useful in offering the best personalized clinical approach. In 2013, the VULvar CANcer Multi‐Disciplinary Team (Vul.Can MDT) was set up in our institution, in order to share knowledge and expertise, high‐quality diagnosis, and evidence‐based decision making in the context of personalized medicine. The aim of this observational study was to report on our series of vulvar cancer patients managed postoperatively with radiotherapy within the framework of a formal multidisciplinary tumor board. Methods : Coupling surgical and oncological international guidelines with "case‐by‐case" discussions, a multi‐specialist consensus was progressively reached and internal recommendations were developed and introduced in the daily routine. Data from vulvar cancer patients who underwent primary surgery and adjuvant radiotherapy throughout a 5‐year period were retrospectively collected. Actuarial local control was the primary endpoint, while secondary end‐points were acute and late toxicities, disease‐free survival, and overall survival. Toxicity was evaluated according to the Common Toxicity Criteria Adverse Event v 4.0 scale. Results : The analysis included 35 patients with squamous vulvar cancer treated with adjuvant radiotherapy±chemotherapy, from April 2013 to September 2017. Median age was 70 years (range 18‐87), all patients underwent surgery followed by concomitant chemoradiation (45.7%) or radiotherapy alone (54.3%). The median prophylactic dose on lymphatic drainage was 45 Gy, while positive nodes and perineal area received 51.2 Gy and 52.6 Gy, respectively. Chemotherapy involved the cisplatin‐based regimen (45.7%)±5‐fluorouracil (37.1%). Median follow‐up was 32 months (range 6‐72): the 24‐months local control, disease‐free survival, and actuarial overall survival rates were 88.6%, 82.0%, and 91.0%, respectively. Low rates of severe acute (12%) and late (3%) toxicities occurred. Discussion : The outcomes of this series support the benefit of a multidisciplinary personalized approach in the management of vulvar cancer.